2004
DOI: 10.1074/jbc.m305531200
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on Origin Recognition Complex containing Orc5p with defective Walker A Motif

Abstract: Orc5p is one of six proteins that make up the origin recognition complex (ORC), a candidate initiator of chromosomal DNA replication in eukaryotes. To investigate the role of ATP binding to Orc5p in cells, we constructed orc5-A, a strain of Saccharomyces cerevisiae having a mutation in the Walker A motif of Orc5p (K43E). The strain showed temperature-sensitive growth. Incubation at a nonpermissive temperature (37°C) caused accumulation of cells with nearly 2C DNA content. Overproduction of Orc4p, another subun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 42 publications
3
24
0
Order By: Relevance
“…Because Orc5-Ap showed decreased affinity for Orc4p by yeast two-hybrid analysis (36), one possibility is that the mutation in ORC-5A affects its interaction with Orc4p in a manner that is independent of ATP binding to Orc5p, which is responsible for its instability in cells. Supporting this notion, we have previously shown that overexpression of Orc4p suppresses the growth defect phenotype of the orc5-A strain (33) but not that of the orc2-5d strain (data not shown in this paper). One remaining unsolved question is whether the defect in ATP binding to Orc5p is responsible for the phenotype exhibited by the orc2-5d strain, such as a slow G 1 -S transition, induction of phosphorylation of Rad53p, and inefficient loading of MCM onto chromatin.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Because Orc5-Ap showed decreased affinity for Orc4p by yeast two-hybrid analysis (36), one possibility is that the mutation in ORC-5A affects its interaction with Orc4p in a manner that is independent of ATP binding to Orc5p, which is responsible for its instability in cells. Supporting this notion, we have previously shown that overexpression of Orc4p suppresses the growth defect phenotype of the orc5-A strain (33) but not that of the orc2-5d strain (data not shown in this paper). One remaining unsolved question is whether the defect in ATP binding to Orc5p is responsible for the phenotype exhibited by the orc2-5d strain, such as a slow G 1 -S transition, induction of phosphorylation of Rad53p, and inefficient loading of MCM onto chromatin.…”
Section: Discussionsupporting
confidence: 58%
“…Because our previous yeast two-hybrid analysis showed that Orc2p has a strong interaction with Orc5p (36), it is possible that phosphorylation of Orc2p affects the structure of Orc5p resulting in it losing its affinity for ATP. We recently reported that ORC-5A (ORC containing a mutant Orc5p with a defective Walker A motif) is unstable in cells due to degradation by the ubiquitin-proteasome system (33,34). However, we have shown here that ORC2-5D is stable in cells.…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…Orc5 is one of the ORC subunits, and ATP binding to Orc5 is involved in efficient ORC formation (Siddiqui and Stillman, 2007;Takahashi et al, 2004). Orc5 has also been implicated in silencing at the HML and MHR loci in yeast and in heterochromatin organization in human cells (Dillin and Rine, 1997;Prasanth et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In S. cerevisiae and Drosophila the ATP-binding activity of Orc1 is essential and regulates DNA binding. Although not essential, mutations in the S. cerevisiae Orc5 ATP-binding motif cause defects in the apparent complex stability (Takahashi et al, 2004). In contrast, mutations of the Orc1, Orc4 or Orc5 ATP-binding motifs inhibit the ability of human ORC to activate replication in ORC-depleted Xenopus egg extracts (Giordano-Coltart et al, 2005).…”
Section: Origin Recognition Complexmentioning
confidence: 99%